Developing of Pteridophyte smart card as ferns learning media based on playing card - Wawan Wahyudi Efendi; A. Atiqoh; Hari Karyono (University of Muhammadiyah Malang, 2023)
Many ferns learning in higher education were organized conventionally and relied only on textbooks. Moreover, it is not in accordance with the characteristics or learning styles of Generation Z (Gen Z). This research aims to produce Pteridophyte Smart Cards (PSC) as a learning media by integrating cards containing real images of ferns with QR Code technology connected to Google Drive. This research and development uses the ADDIE model. This research involved three experts to validate the product's validity. As many as 26 Biology Education students at the University of Muhammadiyah Malang were involved as research subjects and were divided into six groups in the small group practicality test. Furthermore, there are 20 students taking charge to test the product's practicality and attractiveness. The instruments used were questionnaires, observation, and interview sheets. The results show that the product feasibility was 96.67%, media 97.06%, and design 94.44%, so it was declared very feasible. Based on the results of the practicality test, it is classified as a very practical category because the results of the small group test received a score of 85.71% and the class test was 90.89%. The attractiveness test results were 91.25% so it was declared that the products are very attractive. Therefore, it can be used as a learning media for ferns that are interesting, fun, and in accordance with the characteristics or learning styles of Gen Z students.